(untitled) (Indian Journal of Animal Production and Management, 2024)
The colostrum production by buffaloes during 12 h after post birth was measured in three intervals within 2 h after birth, 2 to 6 h after birth, and 12 h after birth, by weigh-suckle-weigh method and hand milked colostrum measured in measuring cylinder. Average colostrum suckled by neonatal calf of having average body weight 27.93 kg in first feeding at 2 h, 2nd feeding at 6 h and 3rd feeding at 12 h after birth were 275.63 mL, 413.13 mL and 656.31mL respectively and average total colostrum suckled by neonatal calves at 6 hours after birth calving and total colostrums suckled in 12 h after birth were 688.76 mL and 1345 mL respectively, with a total yield of 4112 mL of colostrum (suckled plus hand milked) equal to 14.72 % of body weight of the calf. It was found that the total colostrums yield at 6 h and 12 h of after birth (including hand milked and colostrums suckled) were 2252.40 mL and 1867.63 mL, respectively. It was recorded that, average colostrums suckled (per cent of body weight of calf) at 2 hours in first feeding, at 6 hours in 2nd feeding and at12 hours in 3rd feeding of after birth were 1.26, 1.47, and 2.46, respectively and average total colostrums suckled (per cent of body weight of calf) at 6 h after birth (including 1st feeding and 2nd feeding) and at 12 h after birth (includes all three feedings up to 12 h after birth) were, 2.34 and 6.68, respectively.